Implementasi Pembulatan Desimal ke Bawah Keterwakilan Perempuan di KPU Kabupaten Bandung Perspektif Siyasah Dusturiyah - Muhammad Rafi Nur Akbar; Chaerul Shaleh; Aji Saptaji (Jurnal Hukum Lex Generalis, 2025)
The KPU as the respondent in the Supreme Court decision, as previously explained, was ordered to amend Article 8 paragraph (2) of PKPU 10/2023, this was not followed up by the KPU. Instead of revising the regulations, the KPU decided to make an official letter containing a request to Political Parties to comply with the Supreme Court decision, the implications of this Article make the list of permanent candidates for female DPRD members of Bandung Regency many less than 30% in each electoral district, The method used by researchers in this study is the Empirical Normative Legal Method which uses a normative or binding and regulatory rule or law which is combined with factual empirical data. The results of the study show that the KPU did not comply with the Supreme Court decision to revise Article 8 paragraph 2, The implications of rounding the decimal down caused 33 electoral districts on the list of permanent candidates for DPRD members from 18 contesting parties to be less than 30% female representation. From the perspective of the industrial policy, there is no prohibition regarding women in politics or becoming a leader, especially if what a woman is fighting for are good things and things that are beneficial for everyone.